REVIEW TEKNIK BUDIDAYA UDANG PADA TAMBAK PLASTIK (BUSMETIK) - Ammar Fatalattof. A; Ayi Yustiati; Yuli Andriani (Jurnal Media Akuakultur Indonesia, 2022)
Shrimp cultivation has always been a star in the world of Indonesian aquaculture and today it is still one of the national priority aquaculture commodities. The market needs of domestic and foreign shrimp cultivation can be met by the high economic value of shrimp. There are many models of cultivation designs and shrimp farming systems that have been developed and used by farmers ranging from traditional to modern. The development of cultivation technology by utilizing marginal land by using plastic as a container for cultivation maintenance is called "Busmetik" technology, relatively small container sizes between 600m2 - 1000m2 are used in order to encourage young entrepreneurs or those who are new to aquaculture. Shrimp cultivation requires large funds both in investment and operational costs in its activities so that young entrepreneurs become pessimistic in starting a shrimp farming business. The banking sector can be convinced by young entrepreneurs with Busmetik technology because it can provide mutually beneficial solutions between entrepreneurs and banks. There are several things behind this Busmetik technology, namely shrimp which is currently the main focus in the cultivation business, has a stable market, the quality of the environment continues to decline, it is difficult to manage ponds with an area of >2000m2, the types of soil used for pond plots to support the Director General of Aquaculture in the shrimp farming program.